2017
DOI: 10.4067/s0718-221x2017005001001
|View full text |Cite
|
Sign up to set email alerts
|

Decay resistance of wood impregnated with monoethanolamine and sodium bisulfite pulping black liquors

Abstract: The efficacy of monoethanolamine and sodium bisulfite pulping black liquors at three concentrations of 1; 1,5 and 2% on the preservation of poplar wood from white rot (Trametes versicolor) was investigated. The wood specimens were impregnated with the black liquors using a full-cell method. The black liquors enhanced the decay resistance without any reduction in mechanical strength, and a remarkable increase was observed at higher concentrations and weight gain percentage. The performance of monoethanolamine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Since the mass loss is relatively less for treated blocks, it can be inferred that the extract might have formed a protective layer over the surface of wood blocks, at least throughout fungal decay (12 weeks). These results were similar to those previously reported by Nayeri et al (2017), Kwaśniewska-Sip et al (2018), Ouyang et al (2018), Izadyar et al (2020), Ahadnezhad et al (2021). The differences in ML varied depending on the plant extracts and the concentration used.…”
Section: Decay Testsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the mass loss is relatively less for treated blocks, it can be inferred that the extract might have formed a protective layer over the surface of wood blocks, at least throughout fungal decay (12 weeks). These results were similar to those previously reported by Nayeri et al (2017), Kwaśniewska-Sip et al (2018), Ouyang et al (2018), Izadyar et al (2020), Ahadnezhad et al (2021). The differences in ML varied depending on the plant extracts and the concentration used.…”
Section: Decay Testsupporting
confidence: 92%
“…A correlation between retention of extracts (Figure 6), WPG (Figure 7), and ML was also observed as the decay resistance improved with increasing retention and WPG. The results are in line with those reported by Nayeri et al (2017), Kwaśniewska-Sip et al (2018), Ouyang et al (2018), Zelinka et al (2020). The close relationships between dimensional stability and ML (described by second-degree polynomials) are also confirmed by coefficients of determination.…”
Section: Decay Testsupporting
confidence: 92%
“…Karliati et al (2018) reported that the treatment of plywood with BL in PF resins can improve water resistance. A previous study by Nayeri et al (2017) reported that wood laminated with BL as a wood adhesive might not stick to or bind to cell wall components but form a waterinsoluble monoethanolamine polymer.…”
Section: Dimension Stability Pf/bl-impregnated Sc-ctlmentioning
confidence: 99%
“…After impregnation, actual retention (AR) and weight percent gain (WPG) of the treated samples was determined according to the literature (Tascioglu et al 2012;Simsek et al 2013;Mohammadnia Afrouzi et al 2015;Ahmet et al 2017;Nayeri et al 2017;Gupta et al 2021) and by the following Eqs. 1 and 2,…”
Section: Preparation Of Treatment Solutions and Impregnationmentioning
confidence: 99%